The bilateral strength and power asymmetries in untrained boys - Maly, Tomas; Zahalka, Frantisek; Mala, Lucia; Cech, Pavol (Open medicine (Warsaw, Poland), 2015)
The aim of the study was to identify the level of isokinetic strength and power of lower limbs in 13-year-old untrained boys (n=22, height: 158.5±8.0 cm, mass: 49.1±12.6 kg), to determine bilateral deficit between the limbs in the tests and examine their mutual relationship. Maximum peak muscle torque of knee extensors (PTQ) and flexors (PTH) on dominant (DL) and non-dominant leg (NL) were measured by isokinetic dynamometer. Three types of a vertical jump: countermovement jump with (CMJFA) and without arms (CMJ) and squat jump (SJ) were performed on two force platforms. We found the significant effect (p<.01) of independent variables (knee extensors, flexors, AV) and their interaction on PT. AV did not indicate any significant effect on bilateral ratio of knee extensors (F4,84=.74, p>.05, ηp2=0.03), however a significant effect of AV was found in knee flexors (F4,84=2.70, p<.05, ηp2=.114). The type of jump had no effect on the difference between force exerted by DL and NL (F1,21=.102, p>.05, ηp2=.01). Bilateral deficit (Q:Q, H:H) did not significantly correlate with bilateral deficit in jumps (p>.05). Despite the possibility of identifying muscle asymmetries in the sense of strength imbalances, their mutual relationship with results in isokinetic dynamometry and power jump tests is still unclear.
Keywords: vertical jump; imbalance; injury prevention; symmetry; Isokinetic testing; youth; health